Employee dissent on social media and organizational discipline. (May 2020) - Thompson, Paul; McDonald, Paula; O'Connor, Peter
What kind of surveillance of employees is evident today? The rights of employers to police and act punitively with regard to workplace dissent and misbehaviour have become contentious legal, policy and ethical issues. Drawing on survey responses from employees in the UK and Australia, this study investigates the scope and scale of employee dissent in relation to critical online comments and the private use of social media during work time. The findings reveal a sufficient pool of misbehaviours, albeit that they are emergent and uneven. Also evident were some apparently contradictory responses with respect to employer rights to profile and discipline, at the same time as asserting employee rights to voice and private online identities. The findings contribute to knowledge of how much and what kinds of online dissent exist in the ambiguous space between the public sphere of work and the private lives of individual employees and what employers do about it.